Welcome to our community

Be a part of something great, join today!

Why is the following not true: f(f^(-1)(B))=B?

OhMyMarkov

Member
Mar 5, 2012
83
The title says it: why is the following not true: $f(f^{-1}(B))=B$?

Thanks!
 
Last edited by a moderator:

Opalg

MHB Oldtimer
Staff member
Feb 7, 2012
2,713
Re: Why is the following not true: $f(f^{-1}(B))=B$?

The title says it: why is the following not true: $f(f^{-1}(B))=B$?

Thanks!
You have not given a context for this, but in general if you have a function $f:A\to B$ there is no reason to suppose that the range of $f$ is the whole of $B$. If $f$ is not surjective then $f(f^{-1}(B)) = f(A) \ne B$.